2008
DOI: 10.1093/ajcn/88.3.618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex and genotype on cardiovascular biomarker response to fish oils: the FINGEN Study

Abstract: Supplements providing EPA+DHA at doses as low as 0.7 g/d have a significant effect on the plasma lipid profile. The results of the current trial, which used a prospective recruitment approach to examine the responses in population subgroups, are indicative of a greater triacylglycerol-lowering action of long-chain n-3 polyunsaturated fatty acids in males than in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
144
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 49 publications
18
144
3
1
Order By: Relevance
“…Intakes in the range of 0.7-1.5 g/day provided either as oily fish (Griffin et al 2006) or as purified lipids (Caslake et al 2008) in healthy subjects have shown a small effect on lowering TAG (8-11 %) and a 2-3 % increase in LDL-cholesterol concentration. With regard to the plasma lipid profile, we previously found a 15 % reduction in TAG concentration in women after 1.8 g/day, showing a clear dose-response relationship with increasing intakes (P = 0.002), but no significant effect on lipoprotein-cholesterol (Sanders et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Intakes in the range of 0.7-1.5 g/day provided either as oily fish (Griffin et al 2006) or as purified lipids (Caslake et al 2008) in healthy subjects have shown a small effect on lowering TAG (8-11 %) and a 2-3 % increase in LDL-cholesterol concentration. With regard to the plasma lipid profile, we previously found a 15 % reduction in TAG concentration in women after 1.8 g/day, showing a clear dose-response relationship with increasing intakes (P = 0.002), but no significant effect on lipoprotein-cholesterol (Sanders et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid methyl esters were identified by comparison of retention times against known standards, Supelco 37 component FAME mix and PUFA-3 Menhaden oil (Supelco). Due to previous findings that changes in lipid profile in response to DHA supplementation differ between apoE4 carriers v. non-carriers (6,12,13) , phospholipid fatty acid status was analysed with respect to genotype in order to ascertain whether the E4 isoform may alter incorporation of LC n-3 PUFA into phospholipids. To our knowledge, only two studies have examined phospholipid fatty acid status with respect to genotype (6,14) , both with relatively small subject numbers (n 8 carriers, n 20 non-carriers and n 18 carriers, n 20 non-carriers, respectively).…”
Section: Assessment Of Plasma Phospholipid Fatty Acid Statusmentioning
confidence: 99%
“…However, a number of studies are expected to report in the near future, including a prospective study of the impact of apo E genotype on blood lipid responses to fish oil fatty acids, which has also been designed to include equal numbers of both genders in each genotypic sub-group [44]. Evidence of gender-specific differences in response to diet that may be mediated in part by gender-genotype interactions is another factor that has recently been described in a few publications [4,40,45]. Evidence from studies involving functional proteins involved in lipid metabolism as related to cardiovascular disease (apo E), obesity (perilipin) and selenium metabolism (Selenoprotein P) is indicating that the differences in response to dietary modifications associated with specific genetic mutations may affect men and women differently.…”
Section: Genetic Variation and Nutritionmentioning
confidence: 99%